Could HoLEP change the further management of incidental prostate cancer? - Di Gianfrancesco, Luca; Crestani, Alessandro; Amodeo, Antonio; Corsi, Paolo; Miglioranza, Eugenio; De Marchi, Davide; Busetto, Gian Maria; Maggi, Martina; Porreca, Angelo (Frontiers in Urology, 2023)
Introduction Holmium Laser Enucleation of the Prostate (HoLEP) represents an effective and well-established technique in the treatment of lower urinary tract symptoms (LUTS) related to benign prostatic hypertrophy (BPH). We evaluated patients with BPH and concomitant or incidentally detected prostate cancer (PCa) treated with HoLEP and the subsequent clinical management. Materials and Methods We performed a retrospective review of patients treated with HoLEP at a single institution. We analyzed total pre- and postoperative prostate-specific antigen (tPSA), multi-parametric magnetic resonance (mpMRI) imaging, and pathology results in patients with a PCa diagnosis performed before HoLEP (group 1) and incidentally at HoLEP (group 2). Results We analyzed a total of 147 consecutive patients: 16 (10.9%) patients already had a PCa diagnosis before HoLEP, and in 18 (12.2%) patients PCa was incidentally detected at HoLEP. The tPSA level at 3 months after HoLEP dropped by 85.8% (from 14.34 ng/ml to 2.04 ng/ml) in patients of group 1 and by 86.5% (from 3.94 ng/ml to 0.53 ng/ml) in patients of group 2; the values remained stable up to 12 months after HoLEP. By including even those patients who underwent cancer treatment post-HoLEP, all patients in both groups survived without cancer progression (based on their initial PCa status). Conclusions Patients undergoing HoLEP might receive a PCa diagnosis in more than 10% of cases. The HoLEP technique can be performed even in patients with PCa, at any stage of the disease, to treat LUTS. The procedure does not negatively impact oncological outcomes even when PCa is diagnosed before or at HoLEP. Surely, the durability of the success of this approach to management needs further investigation.